Rural and urban differences in the implementation of Virtual Integrated Patient‐Aligned Care Teams. Issue 1 (25th May 2022) - Oh, Anna; Scott, Jennifer Y.; Chow, Adam; Jiang, Hao; Dismuke‐Greer, Clara E.; Gujral, Kritee; Yoon, Jean
Abstract: Purpose: Workforce shortages contribute to geographic disparities in accessing primary care services. An innovative, clinic‐to‐clinic videoconferencing telehealth program in the Veterans Health Administration (VHA) called the Virtual Integrated Patient‐Aligned Care Teams (V‐IMPACT) was designed to increase veterans' access to primary care and relieve workforce shortages in VA primary care clinics, including in many rural areas. This paper describes trends in clinic sites and veteran uptake of the V‐IMPACT program, a model that delivered remote, team‐based primary care services, from fiscal years (FY)2013‐2018. Methods: This observational study used VHA administrative data to compare program uptake, measured by the program penetration rate (percent of patients using V‐IMPACT services in each site) across sites; and characteristics for V‐IMPACT users versus nonusers for 2, 155, 203 veteran‐years in 69 sites across 7 regional networks for FY2013‐2018. Regression models assessed the association between V‐IMPACT use and veteran characteristics within sites. Findings: Across sites, V‐IMPACT had higher penetration in rural sites (8%) and primary care community‐based outpatient clinics (7%, P <.001). After adjusting for veteran characteristics, rural veterans (aOR = 1.05; P = .02) and veterans with higher comorbidity risk scores (aOR = 1.08; P <.001) were independently associated with V‐IMPACT use. Highly rural veterans (OR = 0.60; P <.001) and veterans who lived ≥40 miles from the closest VHA primary care site (OR = 0.86; P <.001) were less likely to be a V‐IMPACT user. Conclusions: A clinic‐to‐clinic telehealth program, such as V‐IMPACT, was able to reach many rural sites, rural veterans, and veterans in primary care health professional shortage areas. V‐IMPACT has the potential to increase access to team‐based primary care.